The Effectiveness of Coordination and Supervision of Civil Servant investigators (PPNS) by Republic of Indonesia Police Investigators in the Jurisdiction of South Sulawesi Regional Police - Nadia Nurul Izmi Dawali; M. Syukri Akub; Nur Azisa (Khazanah Hukum, 2022)
The purpose of this research is to analyze the effectiveness of coordination and controlling of civil servant investigators by Indonesian police investigators in the police icate that the effectiveness of coordination and controlling of civil servant investigators by Police Investigators is still ineffective. In practice, there are difference boundaries of the jurisdictional authority of each institutions and there are different perception in each institutions towards on the criminal investigators process with Police investigators. Meanwhile, the efforts of police investigators to improve the implementation of coordination and controlling function to process criminal investigation by civil servant investigators in the police jurisdiction region south Sulawesi is providing guidance for developing civil servant investigators capability and supervision between the related institutions. The efforts of the police investigators towards civil servant investigators capability development have been effective as it proved held once in every year and the supervision between the related institutions will be held if the head of civil servant investigators institutions make some request. Civil Servant Investigators are expected to maximize the function of coordinating and controlling the investigation with police investigators in this case Korwas Investigators, so that the law enforcement process can run synergistic.